Benchmarks of a III-V TFET technology platform against the 10-nm CMOS FinFET technology node considering basic arithmetic circuits. (February 2017) - Strangio, S.; Palestri, P.; Lanuzza, M.; Esseni, D.; Crupi, F.; Selmi, L.
Abstract: In this work, a benchmark for low-power digital applications of a III-V TFET technology platform against a conventional CMOS FinFET technology node is proposed. The analysis focuses on full-adder circuits, which are commonly identified as representative of the digital logic environment. 28T and 24T topologies, implemented in complementary-logic and transmission-gate logic, respectively, are investigated. Transient simulations are performed with a purpose-built test-bench on each single-bit full adder solution. The extracted delays and energy characteristics are post-processed and translated into figures-of-merit for multi-bit ripple-carry-adders. Trends related to the different full-adder implementations (for the same device technology platform) and to the different technology platforms (for the same full-adder topology) are presented and discussed.